FACTORS RELATED TO THE INCIDENCE OF DENGUE HEMORRHAGIC FEVER, GUNUNG MAS VILLAGE, UPTD GUMAWANG PUSKESMAS, EAST OKU DISTRICT - Emilia; Eva Yustati; Zanzibar (Perhimpunan Ahli Epidemiologi Indonesia, 2023)
ABSTRACTBackground: Dengue hemorrhagic fever is a disease that is transmitted to humans through the bite of infected mosquitoes, especially the Aedes aegypti and Aedes albopictus mosquitoes, which are found in almost all corners of Indonesia. Method: The research design used is a cross-sectional research design. The population in this study is people aged 15–44 years and 55 years in Gunung Mas village, totaling 1,591 people. The sample size in this study was 91 respondents. Results: Based on the analysis results, the Chi Square test results obtained a p value of 0.0005, meaning that there is a significant relationship between knowledge and the incidence of dengue hemorrhagic fever. The results of the Chi Square test showed a p value of 0.0005, meaning that there was a significant relationship between attitude and the incidence of dengue hemorrhagic fever. The results of the Chi Square test showed a p value of 0.0005, meaning that there was a significant relationship between the habit of littering and the incidence of dengue hemorrhagic fever. The Chi Square test results obtained a p value of 0.0005, meaning that there is a significant relationship between SPAL facilities and the incidence of dengue hemorrhagic fever. Conclusion: There is a significant relationship between knowledge, attitudes, habits of littering, and waste water disposal channels and the incidence of dengue hemorrhagic fever.